Au(I)-catalyzed dimerization of two alkyne units - interplay between butadienyl and cyclopropenylmethyl cation: model studies and trapping experiments - Kreuzahler, Mathis; Gleiter, Rolf (The journal of organic chemistry, 2017)
In recent years, Au(I)-catalyzed reactions proved to be a valuable tool for the synthesis of substituted cycles by cycloaromatization and cycloisomerization starting from alkynes. Despite the myriad of Au(I)-catalyzed reactions of alkynes, the mono Au(I)-catalyzed pendant to the radical dimerization of nonconjugated alkyne units has not been investigated by quantum chemical calculations. Herein, by means of quantum chemical calculations, we describe the mono Au(I)-catalyzed dimerization of two alkyne units as well as the transannular ring closure reaction of a nonconjugated diyne. We found that depending on the system and the method used either the corresponding cyclopropenylmethyl cation or the butadienyl cation represents the stable intermediate. This circumstance could be explained by different stabilizing effects. Moreover, the calculation reveals a dramatic (>1012-fold) acceleration of the Au(I)-catalyzed reaction compared to that of the noncatalyzed radical variant. Trapping experiments with a substituted 1,6-cyclodecadiyne using benzene as a solvent at room temperature as well as studies with deuterated solvents confirm the calculations. In this context, we also demonstrate that trapping of the cationic intermediate with benzene does not proceed via a Friedel-Crafts-type reaction.